GAMBARAN STRUKTUR ANATOMIS DAN UJI AKTIVITAS ANTIOKSIDAN DAUN SERTA BATANG Hydroleaspinosa - Putri Vidiasari Darsono (Universitas Lambung Mangkurat, 2012)
This studyaimed toobserve anatomicalstructure and antioxidant activitiesofleavesand stemsHydroleaspinosa. Anatomical tissues section of leaves and stems wereprepared using paraffin method and analysis of antioxidant activities was done by DPPHmethod (1, 1–difenil–2–pikrilhidrazil). The results showed that the anatomical structureofHydroleaspinosaleavescross sectionconsistsofupperepidermis cells(adaksial)andlowerepidermis cells(abaksial), trichomes, mesophyll that was differentiatedintoabovepalisadeparenchymaandbelow spongyparenchyma, vasculartissues, the strengthenertissuesanddruscrystals. While on thecross sectionofthe stems wereepidermis, cortex,vessels, and pith.There wasairspace between medium stemsand old stems. The resultsofanalytical measurements ofantioxidantactivities onethanolextractofHydroleaspinosaleaves with IC50value 52.735ppm are higher than thestemswithIC50value 68.911ppmbutstill lowerthan the controlof vitaminCandBHT.